2020
DOI: 10.1002/tesq.581
|View full text |Cite
|
Sign up to set email alerts
|

Development and Initial Validation of the L2‐Teacher Grit Scale

Abstract: Grit—“perseverance and passion for long‐term goals” (Duckworth, Peterson, Matthews, & Kelly, 2007, p. 1087)—has attracted the attention of researchers in fields ranging from psychology to business to education (e.g., Robertson‐Kraft & Duckworth, 2014; Robins, 2019). Continuing the line of research that explores the domain specificity of grit (e.g., F. T. C. Schmidt, Fleckenstein, Retelsdorf, Eskreis‐Winkler, & Möller, 2017), this study introduces the L2‐Teacher Grit Scale (L2TGS) developed to measure grit spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 54 publications
(84 reference statements)
0
60
0
Order By: Relevance
“…These inconclusive results raise the point that an L2-specific grit scale was needed to act as a more accurate measurement of achievement in an L2 setting (Sudina et al, 2020). Consequently, Teimouri et al (2020) constructed the L2 grit scale to assess the domain-specific grit in SLA.…”
Section: L2 Gritmentioning
confidence: 99%
“…These inconclusive results raise the point that an L2-specific grit scale was needed to act as a more accurate measurement of achievement in an L2 setting (Sudina et al, 2020). Consequently, Teimouri et al (2020) constructed the L2 grit scale to assess the domain-specific grit in SLA.…”
Section: L2 Gritmentioning
confidence: 99%
“…2 In SLA research, on the other hand, the research examining the links between domain-specific grit and L2 achievement has shown promising results. Although the L2 studies that used a domain-general measure of grit have produced somewhat inconsistent findings (Khajavy et al, 2020;Robins, 2019;Wei et al, 2019;Yamashita, 2018), the studies that have used domain-specific grit scales have predominantly found grit as a significant, positive factor in L2 learning and teaching (e.g., Sudina & Plonsky, 2021a, 2021bSudina, Brown, et al, 2021;Sudina, Vernon, et al, 2021;Teimouri et al, 2020). Notably, the effects of domain-general grit versus domain-specific grit on L2 learning have also been scrutinized, and the findings have identified domain-specific grit as having much stronger effects on L2 learning than domain-general grit.…”
Section: Grit As a Predictor Of Success And Performancementioning
confidence: 99%
“…It is noteworthy that the inconclusive results of these studies implied the need for an L2-specific grit scale for a more accurate measurement of the construct in SLA (Sudina et al, 2020). Outside SLA, the domain-general SLA has been criticized in favor of the domain-specific conceptualization of grit (see Clark & Malecki, 2019;Cormier et al, 2019;Schmidt et al, 2017).…”
Section: Domain-specific Gritmentioning
confidence: 99%
“…Within SLA, Teimouri et al (2020) developed the L2-grit scale to measure the domain-specific grit in SLA and argued that such a measure would enhance the validity of grit in SLA. Also, Sudina et al (2020) investigated the factor structure of this scale and showed that the L2-grit scale yielded sufficient internal consistency and a higher predictive validity than the domain-general scale. Although the introduction of the L2 grit scale paved the way for domainspecific studies of the construct (see Khajavy et al, 2020), the body of research in SLA is still lagging behind the dynamic sphere.…”
Section: Domain-specific Gritmentioning
confidence: 99%